Environmental Education Through Fish and Vegetable Farming (Aquaponics) at Menara Fitrah Islamic Elementary School - Mukti, Retno Cahya; Fitrani, Mirna; Meilinda, Meilinda; Haryanto, Muhammad Ravianda Aditya; Zammardi, Syakhain (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Instilling an attitude of environmental care can be done from an early age, namely in elementary school, through direct practice outside the classroom. One activity that can instill an attitude of environmental care is fish and vegetable farming (aquaponics). Menara Fitrah Islamic Elementary School is one of the schools that has adopted an attitude of environmental care, making it a partner in this community service activity. The purpose of this activity is to increase students' attitudes toward caring for the environment through fish and vegetable farming (aquaponics). This community service was carried out using Asset-Based Community Development (ABCD), which involves community service grounded in the community's strengths and potential. Community service activities are carried out through a preparation stage, namely coordination between the implementation team and the school, a socialization stage, and fish farming training for sixth-grade students and science teachers, a mentoring stage through fish and vegetable farming (aquaponics) involving sixth-grade students and students as field practice activities, and an evaluation stage. The results show that the activities carried out can increase students' awareness of the environment and, with direct student involvement in fish and vegetable farming (aquaponics), increase it by 100%.